Effect of Video Games on Psychological Development of the Child in Primary Schools in Baghdad - Siham A. Hammo (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: To review scientific studies of the effect of video games on child psychological development.And to examine the evidence that playing video games plays a role on child psychological development.Design: A descriptive analytical study starting from December 2016 to May 2017 such an assessmentapproach is apply to achieve the objectives of the study.Methodology: A simple random sample of 300 students selected from a probability-stratified sample ofprimary school for both sexes in Baghdad Al – Rasafa, starting from December 2016 to May 2017. Aquestionnaire constructed for the purpose of the present study throughout a review of relevant literature,previous studies and consultation from panel of experts. To begin, answer the questions using the scale, Know,Uncertain, Don’t Know. The questionnaire consist of two main parts, Part one included the demographicinformation (15) items, part two included the items of psychological effect which consist of (13) items.The overall items which were included in the questionnaire were (28) items. Reliability and validity of thequestionnaire were determined through a pilot study. Data collected using the questionnaire fromFebruary 27 2017 to 14th of March 2017 through the utilization of the semi - structured technique as amean of data collection. Data analyzed through descriptive statistical data analysis approach (frequency,percentage and mean) and inferential statistical data analysis approach.Results: The results showed that the effect of video games on the psychological development of the childhad a mild significant effect resulting from playing video games.Conclusion: It is clear that the effect of video game is a serious problem for the generation of children andfuture builders in our society, when there is no aware towards the impact of the problem. Recommendation: Educating children about media effects generally and about video game effectsspecifically, so that children can learn to make informed choices. In addition, encouraging children to playpro-social and educational video games in preference to violent games.